Tax avoidance and vertical interlocks within multinational enterprises - Henning Giese; Reinald Koch; Markus Gamm (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
This study investigates to what extent multinational enterprises appoint managers jointly at the headquarter and a foreign subsidiary (vertical manager interlocks, VMIs) in order to facilitate tax planning. We use a cross-section data set taken from the AMADEUS database to show that VMIs are observed more frequently in MNEs with a higher potential for tax-induced profit shifting. We also provide evidence indicating that the implementation of VMIs is motivated by an internal principal-agent conflict arising from conflicting interests between the MNE and high-tax subsidiary managers. Finally, we show that the use of VMI structures is associated, ceteris paribus, with a lower effective tax rate.
Keywords: H25; H26; M12; 330; management structure; profit shifting; principal-agent-theory